Para além de uma questão feminina: a opressão das mulheres na sociabilidade do capital - Marília Duarte de Souza (2024)
We defend the thesis that the oppression of women in capitalism is determined by the relationship of sexual division of labor subsumed in the process of production and valorization of value. In the meantime, variations in the form and intensity of this relationship are verified depending on the needs assumed by capital in different historical contexts and the moment in which capitalist accumulation is found (Saffioti, 1976), which is expressed in a non-linear movement of advancement in changing the reality of women's subjugation, but a contradictory movement of advances and setbacks. In this sense, let us consider that, in times of capital crisis, the need to intensify exploitation demands a process of more intense lowering of the value of labor power and the intensification of relations of oppression in general and the oppression of women in particular, can be an aspect activated by the capitalist system to assist in this movement in at least two aspects: in the movement of retraction of labor forces and increase of the industrial army; in the greater demand for reproductive work, which engenders greater availability of working women to carry out such activities free of charge for the working class. Thus, we seek to analyze the impacts of the last major global economic crisis, which began to be felt more intensely in Brazil, especially from 2013, on the material living and working conditions of Brazilian women workers. It was possible to analyze that the impact resulting from the economic and political crisis hits women workers even more intensely, who experience higher rates of unemployment, informality and a significant decrease in average wages, in addition to a significant increase in all forms of violence against women. from 2013, especially domestic violence (IPEA, 2022; IBGE, 2022). There is also a retreat by the State in the provision of public policies aimed at women's economic and social autonomy, and the direction of policies towards strengthening the transfer of reproductive activities to the family, therefore, we see a strengthening of the institution family and the sexual division of labor mediated by what is conventionally called “conservative morality”. Through the analyzes and data presented, we conclude that, despite being important, the advances achieved, on the one hand, have not guaranteed concrete changes in the relations of subjugation of women by men, on the other hand, that they are not fixed achievements, but constitute a movement of advances and setbacks, as seen in the last decade. In this sense, we believe that only the liberation of working women and working men from the self-alienation of work frees human beings from the existing conditions of exploitation and oppression, by overcoming the split posed by private ownership of the means of production that constituted the new bases concrete means of oppression.